Baricitinib against severe COVID-19: effectiveness and safety in hospitalised pretreated patients. (28th July 2021) - Iglesias Gómez, Rubén; Méndez, Raúl; Palanques-Pastor, Tomás; Ballesta-López, Octavio; Borrás Almenar, Conxa; Megías Vericat, Juan Eduardo; López-Briz, Eduardo; Font-Noguera, Isabel; Menéndez Villanueva, Rosario; Román Iborra, José Andrés; Poveda Andrés, José Luis
Abstract : Objectives: To analyse the effectiveness and safety of baricitinib for severe COVID-19 in cytokine storm syndrome based on its potential role as an anti-inflammatory immunomodulator and inhibitor of viral endocytosis. Methods: This was an observational retrospective study of hospitalised patients treated with baricitinib for severe COVID-19. Outcomes were clinical improvement on an ordinal scale of 1–8 on day 1 of baricitinib compared with day 14 (where 8=death and 1=not hospitalised with no limitations of activities), overall survival, time to recovery since baricitinib treatment started (days until hospital discharge) and laboratory parameters related to COVID-19 poor prognosis. Adverse events related to baricitinib during the admission period were also reported. Results: Forty-three patients (70% men, mean age 70 years (IQR 54–79)) treated with baricitinib daily for 6 days (IQR 5–7) were included. Thirty-six patients were treated with corticosteroids (84%). Clinical improvement was 3 points (IQR 1–4) in patients on an ordinal scale of 4–6, overall survival was 100% at day 30 and day 60 with a mean time to recovery of 12 days (IQR 9–25) from start of baricitinib treatment. No adverse events of interest were found and all poor prognosis risk factors improved at day 14: interleukin-6, C-reactive protein, ferritin, lymphocytes, platelets and D-dimers. Conclusions: Patients treated with baricitinib for severe COVID-19 showed improvements in clinical and analytical values without relevant adverse events and 100% overall survival. Clinical randomised trials are needed to confirm the clinical benefit of baricitinib.